Multicenter evaluation of the safety and efficacy of radioembolization in patients with unresectable colorectal liver metastases selected as candidates for 90Y resin microspheres - Kennedy, Andrew S.; Ball, David; Cohen, Steven J.; Cohn, Michael; Coldwell, Douglas M.; Drooz, Alain; Ehrenwald, Eduardo; Kanani, Samir; Rose, Steven C.; Nutting, Charles W.; Moeslein, Fred M.; Savin, Michael A.; et al. (Journal of Gastrointestinal Oncology; Vol 6, No 2 (April 13, 2015): Journal of Gastrointestinal Oncology, 2015)
Background: Metastatic colorectal cancer liver metastases Outcomes after RadioEmbolization (MORE) was an investigator-initiated case-control study to assess the experience of 11 US centers who treated liverdominant metastases from colorectal cancer (mCRC) using radioembolization [selective internal radiation therapy (SIRT)] with yttrium-90-(90Y)-labeled resin microspheres. Methods: Data from 606 consecutive patients who received radioembolization between July 2002 and December 2011 were collected by an independent research organization. Adverse events (AEs) and survival were compared across lines of treatment using Fisher’s exact test and Kaplan-Meier estimates, respectively. Results: Patients received a median of 2 (range, 0-6) lines of prior chemotherapy; 35.1% had limited extrahepatic metastases. Median tumor-to-liver ratio and -activity administered at first procedure were 15% and 1.17 GBq, respectively. Hospital stay was 0.05). Median survivals [95% confidence interval (CI)] following radioembolization as a 2nd-line, 3rd-line, or 4thplus line were 13.0 (range, 10.5-14.6), 9.0 (range, 7.8-11.0), and 8.1 (range, 6.4-9.3) months, respectively; and significantly prolonged in patients with ECOG 0 vs. ≥1 (P=0.009). Statistically significant independent variables for survival at radioembolization were: disease stage [extrahepatic metastases, extent of liver involvement (tumor-to-treated-liver ratio)], liver function (uncontrolled ascites, albumin, alkaline phosphatase, aspartate transaminase), leukocytes, and prior chemotherapy. Conclusions: Radioembolization appears to have a favorable risk/benefit profile, even among mCRC patients who had received ≥3 prior lines of chemotherapy.